Laser transfer film
The existing solution is to form a thermal expansion dome with high light transmittance and uniform size in the laser power range of 0.5W to 10W by using a substrate film of inorganic and organic particles and a thermally expandable light absorbing layer of inorganic and organic particles in the laser transfer film. In the technology, the problem of uneven size of the laser transfer film in the laser power range has achieved precise transfer of the transfer body.
Patent Information
- Application Number
- CN202380042132.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-25
- Filing Date
- 2023-04-14
- Publication Date
- 2025-01-03
AI Technical Summary
It is difficult for the existing laser transfer film to maintain a high light transmittance and uniform expansion structure within a wide laser power range, affecting the precise transfer of the transfer body.
The substrate film contains inorganic particles and organic particles. The thermally expanded light absorbing layer and the adhesive layer are irradiated by laser light to form a thermally expanded dome, ensuring high light transmittance and dimensional uniformity within the laser power range of 0.5W to 10W, forming 70 one or more thermally expanded domes.
An expanded structure with a high transmittance and uniform size of the substrate film over a wide laser power range is realized, ensuring that the transfer body can be effectively transferred to the desired position of the receiver.
Smart Images

Figure CN119255918A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a laser transfer film. Background Art
[0002] The laser transfer film includes a base film that maintains the film shape, a heat-expandable light-absorbing layer that expands by absorbing laser light, and an adhesive layer.
[0003] The method of transferring the transfer body using the laser transfer film is to selectively expand the heat-expandable light absorbing layer by irradiating the laser located above the base film while maintaining a gap between the laser transfer film and the receiving body, thereby transferring the transfer body adhered to the adhesive layer to the receiving body.
[0004] The heat-expandable light-absorbing layer forms an expanded structure in a bulging shape by laser irradiation. If the transfer body is to be effectively transferred to the desired position on the receiving body, the substrate film needs to have high light transmittance when irradiated with laser, and the size of the expanded structure should be uniform within a wide laser power range.
[0005] Therefore, there is a need for a laser transfer film having high substrate film transmittance and uniformly sized expanded structures over a wide range of laser powers to effectively transfer a transfer body to a desired location on a receiver. Summary of the invention Technical issues
[0006] Therefore, one aspect provides a laser transfer film having high substrate film transmittance and uniformly sized expanded structures within a wide range of laser power to effectively transfer a transfer body to a desired position on a receiver. Technical Solution
[0007] According to one aspect, a laser transfer film is provided, which may include:
[0008] Base film;
[0009] a heat-expandable light-absorbing layer; and
[0010] Adhesive layer,
[0011] Wherein, at least one surface of the substrate film includes one or more particles of inorganic particles and organic particles,
[0012] When a laser having a wavelength of 1064 nm is irradiated on the substrate film for a time of less than or equal to 1 second at a laser power range of 0.5 W to 10 W, the heat-expandable light-absorbing layer and the adhesive layer expand to form a heat-expandable dome.
[0013] The thermal expansion dome has a height-to-diameter ratio of 0.1 to 1.
[0014] When a region where 100 heat expansion domes are to be formed is irradiated with a picosecond laser or a nanosecond laser at a laser power range of 0.5 W to 10 W, the heat expandable light absorbing layer and the adhesive layer may form 70 or more heat expansion domes.
[0015] The light transmittance of the substrate film at a wavelength of 550 nm may be greater than or equal to 85%.
[0016] The ten-point average roughness (Rz) of the surface of the substrate film may be 0.5 μm to 8 μm.
[0017] The particles may include inorganic particles comprising one or more selected from silicon dioxide, calcium carbonate, titanium carbide, and zirconium oxide; or
[0018] The organic particles contain one or more selected from styrene resin, acrylic resin, olefin resin, and copolymer resins thereof.
[0019] The thermal conductivity of the particles may be greater than or equal to 1.4 W / m·K.
[0020] The substrate film may include:
[0021] A polyester resin core layer; and
[0022] A polyester resin outer layer, which comprises one or more inorganic particles and organic particles on at least one surface of the polyester resin core layer,
[0023] The content of the particles can be 100% by weight of the polyester resin included in the core layer and the outer skin layer. The amount is calculated to be 0.01 to 1.0 wt%.
[0024] The heat-expandable light-absorbing layer may include a binder and a light absorber,
[0025] The light absorber may include a near infrared absorption dye having a maximum absorption wavelength of 900 nm to 1200 nm.
[0026] The light absorber may be included in an amount of 0.1 parts by weight to 30 parts by weight based on 100 parts by weight of the heat expandable light absorbing layer.
[0027] The coating amount of the heat-expandable light-absorbing layer after drying may be 0.5 g / m 2 Up to 9g / m 2 .
[0028] The heat-expandable light-absorbing layer may have a thickness of 0.4 μm to 10 μm.
[0029] The heat-expandable light-absorbing layer and the adhesive layer can be separated by expansion to form a plurality of heat-expandable domes.
[0030] The diameter deviation of the plurality of thermal expansion domes according to the following formula 1 may be less than or equal to 10%:
[0031] [Formula 1]
[0032] Diameter deviation (%) = │{(average diameter)-(measured diameter)} / (average diameter)×100│
[0033] The height deviation of the plurality of thermal expansion domes according to the following formula 2 may be less than or equal to 10%:
[0034] [Formula 2]
[0035] Height deviation (%) = │{(average height)-(measured height)} / (average height)×100│
[0036] The thickness of the adhesive layer may be 0.5 to 6 times the thickness of the heat-expandable light-absorbing layer.
[0037] The invention may further include a transfer body bonded to the surface of the adhesive layer.
[0038] The transfer body may include a semiconductor chip. Beneficial Effects
[0039] The laser transfer film according to one aspect has a high light transmittance of the base film and a uniformly sized expanded structure within a wide range of laser power, so that the transfer body can be efficiently transferred to a desired position on a receiving body. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 is a cross-sectional view of a laser transfer film according to one embodiment.
[0041] Figure 2 This is a three-dimensional optical microscope image of the substrate film surface of the laser transfer film produced in Example 1.
[0042] Figure 3 This is a three-dimensional optical microscope image of the substrate film surface of the laser transfer film produced in Comparative Example 1.
[0043] Figure 4 It is a diagram used to describe the role and effect of laser transfer film.
[0044] Figure 5 This is a scanning electron microscope image of the laser transfer film produced in Example 1. DETAILED DESCRIPTION
[0045] The laser transfer film is described in detail below through the embodiments of the present invention and the accompanying drawings. It is obvious to those skilled in the art that these embodiments are only for describing the present invention in more detail, and the scope of the present invention is not limited thereto.
[0046] All technical and scientific terms used in this specification have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs, unless otherwise defined. In the event of a conflict, the definitions included in this specification shall prevail.
[0047] Methods and materials similar or equivalent to those described in this specification can be used in the practice or experimentation of the present invention, but appropriate methods and materials are described in this specification.
[0048] In this specification, the meaning of "at least one side" before a constituent element includes "one side" or "both sides" of the above constituent element. In this specification, "at least one", "one or more" or "one or more" before a constituent element means that the list of the entire constituent elements can be supplemented and does not mean that each constituent element described above is supplemented.
[0049] The term "and / or" in this specification means any and all combinations of one or more of the listed items described. The term "or" in this specification means "and / or".
[0050] The term "comprising" in this specification is used to indicate that other constituent elements may be added or / and sandwiched, but other constituent elements are not excluded unless otherwise defined. The term "combination thereof" in this specification is used to indicate a mixture or alloy of two or more of the above constituent elements. In this specification, the term "~ type resin" is used to indicate that "~ resin" is included. or / and a broad concept of "derivatives of ~ resin".
[0051] In the present specification, the unit "parts by weight" means a weight ratio between each component unless otherwise defined.
[0052] In this specification, when it is mentioned that a component is disposed "on (on)" another component, the component is directly disposed on the other component, or there is a component interposed between the components. On the contrary, when it is mentioned that a component is disposed "directly" on (on)" another component, there may be no interposed component.
[0053] In this specification, the "laser transfer film" refers to a film that expands due to heat when irradiated with laser light, and transfers a transfer body bonded to the laser transfer film to a receiving film.
[0054] In this specification, the "transferred body" refers to an article that is transferred from a laser transfer film to a receiving film.
[0055] In this specification, "thermal expansion property" refers to the property of expansion due to heat.
[0056] In the present specification, the "heat-expandable dome" refers to a convex structure formed by the expansion of the heat-expandable light-absorbing layer and the adhesive layer, and includes a geometrically complete hemispherical structure or a convex structure similar thereto.
[0057] A laser transfer film according to one embodiment includes a base film, a heat-expandable light-absorbing layer, and an adhesive layer in this order. Wherein, at least one surface of the substrate film includes one or more of inorganic particles and organic particles. When a laser with a wavelength of 1064nm is irradiated above the substrate film for a time greater than or equal to 1 second within a laser power range of 0.5W to 10W, the thermally expandable light absorbing layer and the adhesive layer expand to form a thermal expansion dome, and the aspect ratio of the thermal expansion dome can be 0.1 to 1.
[0058] Since the laser transfer film is formed on the surface layer with a height-to-diameter ratio of 0.5W to 10W in a wide laser power range, 1 to 1 thermal expansion dome, so the transfer body can be effectively transferred to the desired position on the receiver.
[0059] Figure 1 is a cross-sectional view of a laser transfer film according to one embodiment.
[0060] Reference Figure 1 According to an embodiment, the laser transfer film 10 may include a base film 11 , a heat expandable light absorbing layer 12 , and an adhesive layer 13 in sequence.
[0061] The function of the substrate film 11 is to support other functional layers, such as the heat-expandable light-absorbing layer 12, the adhesive layer 13, and the transfer body (e.g., LED chip) optionally bonded to the adhesive layer, as other layers constituting the laser transfer film during a series of processes such as (i) manufacturing the laser transfer film, (ii) laminating the laser transfer film and the receiving film, and (iii) removing the laser transfer film from the receiving film after the transfer is completed.
[0062] The substrate film 11 may generally be a polymer film.
[0063] The polymer film may be both light-transmissive and thermally stable.
[0064] The polymer film may include a polycarbonate resin, a polyolefin resin, a polyethylene resin, a polyester resin, or a combination thereof. For example, the polymer film may be a polyester resin. The polyester resin may include a linear polyester. For example, the polyester resin may use polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, or polyethylene 2,6-naphthalate (PEN) and the like.
[0065] The polyester-based substrate may be a polyester resin obtained by condensing aromatic dicarboxylic acid and aliphatic glycol. The aromatic dicarboxylic acid may be, for example, isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalene dicarboxylic acid, adipic acid, sebacic acid, or hydroxycarboxylic acid. The aliphatic glycol may be, for example, ethylene glycol, diethylene glycol, propylene glycol, butanediol, 1,4-cyclohexanedimethanol, or neopentyl glycol. The polyester resin may be a combination of two or more of the aromatic dicarboxylic acids and aliphatic glycols described above, or a copolymer containing a third component.
[0066] The polyester resin substrate film may use a uniaxial or biaxially oriented film having high transparency, excellent production efficiency and processability.
[0067] The light transmittance of the substrate film 11 at a wavelength of 550 nm may be greater than or equal to 85%. The substrate film 11 has a high light transmittance. Therefore, the position of the transfer body bonded to the surface layer of the laser transfer film 10 can be accurately confirmed by the vision of the laser device.
[0068] The base film 11 may include one or more of inorganic particles and organic particles. The base film 11 may include one or more of inorganic particles and organic particles on at least one surface.
[0069] The ten-point average roughness (Rz) of the surface of the substrate film 11 may be 0.5 μm to 8 μm. When the ten-point average roughness (Rz) of the surface of the substrate film 11 is less than 0.5 μm, the expansion effect caused by the laser may be low, and when the ten-point average roughness (Rz) of the surface of the substrate film 11 is greater than 8 μm, there may be a problem of decreased light transmittance due to increased haze.
[0070] The particles may be inorganic particles selected from one or more of silicon dioxide, calcium carbonate, titanium carbide and zirconium oxide. The inorganic particles may be in any shape such as spherical, blocky, rod-like or plate-like, but are not limited thereto. In addition, the hardness, specific gravity and color of the inorganic particles are not limited. Two or more inorganic particles may be used in combination as needed. For example, the inorganic particles may be silicon dioxide particles.
[0071] Alternatively, the particles may include organic particles, which include one or more selected from styrene resins, acrylic resins, olefin resins, and copolymer resins thereof. Examples of acrylic resins may include polymers or copolymers (co)polymerized from acrylic or methacrylic acid monomers, such as acrylates, methyl methacrylate, ethyl methacrylate, isobutyl methacrylate, n-butyl methacrylate, n-butyl methyl methacrylate, etc. Examples of olefin resins may include polymers or copolymers (co)polymerized from monomers such as ethylene or polypropylene. The organic particles may be homopolymers, or may include multi-layer multi-component (co)polymers coated with other types of monomers on homopolymers. For example, the organic particles may be polymethyl methacrylate particles.
[0072] The thermal conductivity of the particles may be greater than or equal to 1.4 W / m·K. When the thermal conductivity of the particles is high as described above, the heat generated in the light-to-heat conversion layer can be effectively transferred to the surface of the substrate film, so that a thermal expansion dome having an aspect ratio of 0.1 to 1 can be easily formed on the surface layer of the laser transfer film 13. In addition, when a primer layer is formed on the surface of the substrate film 11, a resin containing particles can be used to increase the particle content on the surface of the substrate film 11.
[0073] The substrate film 11 may include a polyester resin core layer; and a polyester resin outer skin layer including one or more particles of inorganic particles and organic particles on at least one surface of the polyester resin core layer, wherein the content of the particles may be 0.01 wt % to 1.0 wt % based on 100 wt % of the polyester resin included in the core layer and the outer skin layer.
[0074] When the content of the particles is less than 0.01 wt % based on 100 wt % of the polyester resin included in the core layer and the outer skin layer, the movement characteristics and coating properties of the substrate film 11 may be deteriorated, and when greater than 1.0 wt %, the surface smoothness of the substrate film 11 may be deteriorated.
[0075] The thickness of the substrate film 11 may be 50 μm to 500 μm, for example, 50 μm to 150 μm. When the thickness of the substrate film 11 is less than 50 μm, it may be deformed by heat during drying, and when the thickness of the substrate film 11 is greater than 500 μm, it may not be hardened due to insufficient heat transfer.
[0076] The substrate film 11 may be primer treated to improve adhesion to the heat expandable light absorbing layer 12, or may be stretched, heat treated or waterproofed to improve thermal stability, or may contain a small amount of microparticles or fillers or be waterproofed to adjust light transmittance.
[0077] When a laser having a wavelength of 1064 nm is irradiated on the substrate film 11 for a time greater than or equal to 1 second within a laser power range of 0.5 W to 10 W, the heat-expandable light-absorbing layer 12 and the adhesive layer 13 may form a heat-expandable dome. The height-to-diameter ratio of the heat-expandable dome may be 0.1 to 1. When the height-to-diameter ratio of the heat-expandable dome is less than 0.1, the heat-expandable light-absorbing layer 12 and the adhesive layer 13 are difficult to expand and thus cannot form a heat-expandable dome. When the height-to-diameter ratio of the heat-expandable dome is greater than 1, the light-to-heat conversion layer and the adhesive layer may be broken.
[0078] When the region where 100 heat expansion domes are to be formed is irradiated by picosecond laser or nanosecond laser in the laser power range of 0.5 W to 10 W, 60 or more heat expansion domes can be formed on the heat expandable light absorbing layer 12 and the adhesive layer 13. When the region where 100 heat expansion domes are to be formed is irradiated by picosecond laser or nanosecond laser in the laser power range of 0.5 W to 10 W for several milliseconds, 60 or more heat expansion domes can be stably formed on the heat expandable light absorbing layer 12 and the adhesive layer 13.
[0079] The heat-expandable light-absorbing layer 12 includes a binder and a light absorber.
[0080] When the laser transfer film is used to transfer the transfer body to the receiving film, the heat expandable light absorbing layer 12 absorbs light (laser) by the light absorber included in the heat expandable light absorbing layer 12 and converts it into heat, thereby providing power to transfer the transfer body to the receiving film.
[0081] The adhesive can exhibit good compatibility with the light absorber and include more of the light absorber in the heat-expandable light-absorbing layer 12 without significantly reducing the adhesion of the heat-expandable light-absorbing layer 12 to the base film 11 .
[0082] The adhesive may include a thermosetting resin.
[0083] The adhesive may include polyester resin, acrylic resin, polyurethane resin, melamine resin, or a combination thereof. For example, the adhesive may be an acrylic resin. The acrylic resin may include polyacrylate, polymethacrylate, polyacrylic acid, a copolymer of each of the substances and a polyolefin, or a combination thereof.
[0084] The light absorber can absorb light in the infrared, visible and / or ultraviolet regions of the electromagnetic spectrum and convert the absorbed light into heat. The light absorber highly absorbs light in the wavelength region or specific wavelength used for transfer, but absorbs significantly less light in other wavelength regions or light other than the specific wavelength by transmitting or reflecting.
[0085] The light absorber may include a near infrared absorption dye having a maximum absorption wavelength of 900 nm to 1200 nm.
[0086] For example, the near-infrared absorbing dye having a maximum absorption wavelength of 900 nm to 1200 nm may include a diimmonium salt-based dye represented by the following Chemical Formula 1:
[0087] [Chemical formula 1]
[0088]
[0089] In the above formula,
[0090] n is 1 or 2;
[0091] R1 to R8 are independently substituted or unsubstituted C1-C10 straight or branched alkyl groups. When R1 to R8 are substituted, The substituent is cyano, nitro, carboxyl, sulfoxy, halogen, hydroxy, C1-C8 alkoxy, alkoxyalkoxy, aryloxy or alkylamino;
[0092] X- is a fluoroalkyl phosphate anion represented by the following Chemical Formula 2.
[0093] [Chemical formula 2]
[0094]
[0095] In the above formula,
[0096] x is 0 or 1;
[0097] y is 1, 2, or 3;
[0098] z is 6-y;
[0099] R9 to R 13 independently of each other is hydrogen or fluorine.
[0100] The content of the light absorber may be 0.1 to 3 parts by weight based on 100 parts by weight of the heat expandable light absorbing layer 12. For example, the content of the light absorber may be 0.5 to 30 parts by weight based on 100 parts by weight of the heat-expandable light-absorbing layer 12. When the content of the light absorber is within the above range, expansion occurs by absorbing light of a laser wavelength, thereby being able to provide a laser transfer film having excellent transfer characteristics.
[0101] The coating amount of the heat-expandable light-absorbing layer 12 after drying can be 0.5 g / m 2 Up to 9g / m 2 For example, the coating amount of the heat-expandable light-absorbing layer 12 after drying may be 1 g / m 2Up to 9g / m 2 , or 2g / m 2 Up to 9g / m 2 , or 3g / m 2 Up to 9g / m 2 When the coating amount of the heat-expandable light-absorbing layer 12 after drying is within the above range, a uniform coating layer can be formed, and thus a laser transfer film having excellent transfer characteristics can be provided.
[0102] From the viewpoint that local heat absorption facilitates transfer, the heat-expandable light-absorbing layer 12 may have a thickness as thin as possible. For example, the heat-expandable light-absorbing layer 12 may have a thickness of 0.4 μm to 10 μm.
[0103] The heat-expandable light-absorbing layer 12 and the adhesive layer 13 are separated by expansion to form a plurality of heat-expandable domes, and the diameter deviation of the plurality of heat-expandable domes according to Formula 1 may be less than or equal to 10%:
[0104] [Formula 1]
[0105] Diameter deviation (%) = │{(average diameter)-(measured diameter)} / (average diameter)×100│
[0106] The height deviation of the plurality of thermal expansion domes according to the following formula 2 may be less than or equal to 10%:
[0107] [Formula 2]
[0108] Height deviation (%) = │{(average height)-(measured height)} / (average height)×100│
[0109] The laser transfer film 10 may further include a transfer body adhered to the surface of the adhesive layer 13 .
[0110] The adhesive layer 13 may play a role in bonding the transfer body to the laser transfer film 10 .
[0111] When the adhesive force of the laser transfer film 10 (specifically, the adhesive force of the adhesive layer) is smaller than the adhesive force of the receiving film, a problem of the transfer body being transferred to the receiving film side occurs when the two films are laminated. On the contrary, when the adhesive force of the laser transfer film 10 is too greater than the adhesive force of the receiving film, a problem of no transfer may occur when the laser is irradiated.
[0112] The adhesive force of the laser transfer film 10 may be 5 gf / in to 500 gf / in (gram-force / inch), and may be adjusted by the adhesive force of the receiving film.
[0113] The adhesive layer 13 may include polyacrylate-based resin, polymethacrylate-based resin, epoxy-based resin, polystyrene-based resin, polyurethane-based resin, polysulfone-based resin, polyester-based resin, polyimide-based resin, polysilicon-based resin, or a combination thereof.
[0114] The thickness of the adhesive layer 13 may be 0.5 to 6 times the thickness of the heat-expandable light-absorbing layer 12 .
[0115] The transfer body may include organic matter, inorganic matter, organic metal or a combination thereof.
[0116] As the transfer body, examples of optionally patterned substances include colorants (including pigments and / or dyes dispersed in a binder), polarizers, liquid crystal materials, particles (including spacers for liquid crystal displays, magnetic particles, insulating particles and / or conductive particles), luminescent substances (including phosphors and / or organic electroluminescent substances), light-receiving substances that can be mixed into light-emitting devices (e.g., electroluminescent devices), hydrophobic substances (including partition banks for inkjet receivers), hydrophilic substances, multilayer stacks (e.g., multilayer device structures such as organic electroluminescent devices), microstructure layers, nanostructure layers, photoresists, metals, polymers, adhesives, binders, biomaterials or combinations thereof.
[0117] The transfer may include one or more substances useful for display applications, particularly for color filter fabrication.
[0118] The transfer body may include a semiconductor chip such as an LED chip.
[0119] Figure 4 It is a diagram for describing the action and effect of the laser transfer film 10 .
[0120] See also Figure 4 The laser transfer film 10 and the receiving film 20 are laminated. The LED chip is bonded to the adhesive layer 13 of the laser transfer film 10.
[0121] The laser is locally irradiated on the laser transfer film 10. At this time, the heat-expandable light-absorbing layer 12 of the laser transfer film 10 generates heat and expands, thereby forming a cavity C between the heat-expandable light-absorbing layer 12 and the adhesive layer 13 and forming a heat-expandable dome by expansion.
[0122] Then, the LED chip 30 bonded to the adhesive layer 13 on the heat-expandable light-absorbing layer 12 moves to the side of the receiving film 20 due to the expansion of the heat-expandable light-absorbing layer 12, and is then adhered to the adhesive layer 23 of the receiving film 20 (which is arranged on the electrode layer 22, and the electrode layer 22 is arranged on the substrate layer 21 of the receiving film 20).
[0123] Then, the LED chip 30 is separated from the adhesive layer 13 of the laser transfer film 10 and then adhered to the adhesive layer 23 of the receiving film 20 .
[0124] As a result, the LED chip 30 is transferred from the laser transfer film 10 to the receiving film 20 .
[0126] Hereinafter, the present invention will be described in further detail by way of examples, but the present invention is not limited thereto.
[0128] [Example]
[0129] Example 1: Manufacturing laser transfer film
[0130] A polyethylene terephthalate resin core layer without particles is formed by a sequential biaxial stretching method, and a polyethylene terephthalate resin outer skin layer containing silica particles (average particle size: 2 μm, thermal conductivity: 1.4 W / m·K) is formed on both sides of the core layer, thereby preparing a polyethylene terephthalate substrate film with a thickness of about 100 μm. At this time, the content of silica particles is 0.01% by weight based on 100% by weight of the polyethylene terephthalate resin included in the core layer and the outer skin layer. The thickness of the core layer is about 90 μm, The thickness of the outer skin layer on both sides was about 5 μm. The ten-point average roughness (Rz) of the outer skin layer was about 0.5 μm.
[0131] Separately, a thermosetting melamine resin (Cymel 303, Cytec Corporation) as an adhesive, a diammonium salt dye (NIR 1000A, Kyung-In Synthetic Corporation) as a light absorber, and a solvent (a mixture of cyclohexanone and methyl ethyl ketone in a weight ratio of 40:100) were mixed to prepare a composition for forming a heat-expandable light-absorbing layer having a solid content of 20% by weight. At this time, the content of the diammonium salt dye was 2 parts by weight based on 100 parts by weight of the heat-expandable light-absorbing layer.
[0132] Separately, a thermosetting acrylic resin (SAMHWA PAINTS, SA3000) and a solvent (a mixture of cyclohexanone and methyl ethyl ketone in a weight ratio of 40:100) were mixed, thereby preparing a composition for forming an adhesive layer having a solid content of 35% by weight.
[0133] The composition for forming a heat-expandable light-absorbing layer was coated on the polyethylene terephthalate substrate film using a Meyer bar, and then thermally dried at 130° C. for 1 minute, thereby forming a coating weight of 3 g / m 2, a heat-expandable light-absorbing layer with an average thickness of 2.3 μm. Then, the composition for forming an adhesive layer was applied on the heat-expandable light-absorbing layer by an applicator, and then the adhesive layer with an average thickness of 2 μm was prepared by heat drying at 110° C. for 2 minutes, thereby preparing a laser transfer film. At this time, the adhesive force of the adhesive layer was 15 gf / inch.
[0135] Example 2: Manufacturing laser transfer film
[0136] A laser transfer film was prepared by the same method as in Example 1 except that the content of the silica particles was 0.02 wt % based on 100 wt % of the entire polyethylene terephthalate resin included in the core layer and the skin layer. At this time, the ten-point average roughness (Rz) of the outer skin layer was about 2.1 μm.
[0138] Example 3: Manufacturing laser transfer film
[0139] A laser transfer film was prepared by the same method as in Example 1 except that the content of the silica particles was 0.1 wt % based on 100 wt % of the entire polyethylene terephthalate resin included in the core layer and the skin layer. At this time, the ten-point average roughness (Rz) of the outer skin layer was about 3.0 μm.
[0141] Example 4: Fabrication of laser transfer film
[0142] A laser transfer film was prepared by the same method as in Example 1 except that the content of the silica particles was 0.5 wt % based on 100 wt % of the entire polyethylene terephthalate resin included in the core layer and the skin layer. At this time, the ten-point average roughness (Rz) of the outer skin layer was about 5.2 μm.
[0144] Example 5: Manufacturing laser transfer film
[0145] A laser transfer film was prepared by the same method as in Example 1 except that the content of the silica particles was 1.0 wt % based on 100 wt % of the entire polyethylene terephthalate resin included in the core layer and the skin layer. At this time, the ten-point average roughness (Rz) of the outer skin layer was about 7.8 μm.
[0147] Example 6: Fabrication of laser transfer film
[0148] In addition to forming a polyethylene terephthalate resin skin layer containing polystyrene particles (PS, average particle size: 2 μm, thermal conductivity: 0.1 W / m·K) on both sides of the polyethylene terephthalate resin core layer, and the content of PMMA particles is 10% of the polyethylene terephthalate resin as a whole including the core layer and the skin layer. A laser transfer film was produced by the same method as in Example 1 except that 0 wt % was 0.01 wt %. At this time, the ten-point average roughness (Rz) of the skin layer was about 0.7 μm.
[0150] Example 7: Fabrication of Laser Transfer Film
[0151] A laser transfer film was prepared in the same manner as in Example 6 except that the content of the particles was 0.5 wt % based on 100 wt % of the polyethylene terephthalate resin included in the core layer and the skin layer. At this time, the ten-point average roughness (Rz) of the skin layer was about 5.5 μm.
[0153] Example 8: Fabrication of Laser Transfer Film
[0154] The content of the PMMA particles is based on the polyethylene terephthalate resin as a whole including the core layer and the outer skin layer. A laser transfer film was produced by the same method as in Example 6 except that 00 wt % was 1.0 wt %. At this time, the ten-point average roughness (Rz) of the skin layer was about 7.6 μm.
[0156] Comparative Example 1: Manufacturing of Laser Transfer Film
[0157] A laser transfer film was prepared by the same method as in Example 1, except that a polyethylene terephthalate resin core layer containing no particles was formed and a polyethylene terephthalate resin skin layer containing no particles was formed on both surfaces of the core layer to prepare a polyethylene terephthalate substrate film having a thickness of about 100 μm. At this time, the ten-point average roughness (Rz) of the skin layer was about 0.2 μm.
[0159] Comparative Example 2: Manufacturing of Laser Transfer Film
[0160] A laser transfer film was prepared by the same method as in Example 1 except that the content of the silica particles was 2.0 wt % based on 100 wt % of the entire polyethylene terephthalate resin included in the core layer and the skin layer. At this time, the ten-point average roughness (Rz) of the outer skin layer was about 12 μm.
[0162] Comparative Example 3: Manufacturing of Laser Transfer Film
[0163] The content of the PMMA particles is based on the polyethylene terephthalate resin as a whole including the core layer and the outer skin layer. A laser transfer film was produced by the same method as in Example 6 except that 00 wt % was 2.0 wt %. At this time, the ten-point average roughness (Rz) of the skin layer was about 10 μm.
[0165] Evaluation example: Evaluation of the physical properties of laser transfer films
[0166] The physical properties of the laser transfer films prepared in Examples 1 to 8 and Comparative Examples 1 to 3 were measured by the following methods: The results are shown in Table 1 below. Figure 2 , Figure 3 ,as well as Figure 5 .
[0167] (1) Substrate film transmittance (%, @550nm)
[0168] The transmittance of the substrate film of each laser transfer film in the range of 300 nm to 1200 nm was measured using a UV-3600 ultraviolet-visible-near-infrared spectrophotometer manufactured by Shimadzu Corporation, and the transmittance at a wavelength of 550 nm was recorded. The results are shown in Table 1.
[0169] (2) Whether the surface of the substrate film contains particles
[0170] The surfaces of the substrate films of the laser transfer films prepared in Example 1 and Comparative Example 1 were observed using a three-dimensional optical microscope to see whether particles were present. The results are shown in Figure 2 and Figure 3 .
[0171] (3) Thermal expansion dome characteristics of the thermally expandable light absorbing layer and the adhesive layer
[0172] For each area of the heat-expandable light-absorbing layer 12 and the adhesive layer 13 where 100 heat-expandable domes are to be formed on the laser transfer film 10, a laser energy ranging from 0.1 W to 10 W is irradiated for several milliseconds (ms) using a Nd:YAG 1064 nm picosecond laser device above the base film 11. A laser scanning device (SUPERSCAN V manufactured by RAYLSE) was used. -15) and using a marking program (welMark 3) to create laser irradiation positions, the laser was programmed and adjusted to irradiate at 10 × 10 positions with a constant pitch (500 μm).
[0173] like Figure 4As shown, the heat-expandable light-absorbing layer 12 and the adhesive layer 13 expand to form a heat-expandable dome TD. The side surface of the formed heat-expandable dome TD was photographed using a scanning electron microscope (SEM).
[0174] Figure 5 is a scanning electron microscope image of the laser transfer film produced by Example 1. Figure 5 It can be confirmed that a plurality of thermal expansion domes are formed on the surface layer of each laser transfer film 10 .
[0175] In addition, similarly to Example 1, the number of thermal expansion domes TD formed on the surface of the laser transfer films prepared in Examples 2 to 8 and Comparative Examples 1 to 3 was counted, and the diameter d and height t were measured. Specifically, for the surface of each laser transfer film, the diameter d and height t of each thermal expansion dome TD formed in an area of 3 cm×3 cm where 100 thermal expansion domes (spacing between TDs: 300 μm) were to be formed were measured, and the aspect ratio was calculated. (t / d) In addition, the average diameter and the average height are calculated from the measured diameter d and height t of each thermal expansion dome TD, and the deviations of the diameter and the height of each thermal expansion dome are calculated by the following equations 1 and 2, respectively. The results are shown in Table 1.
[0176] [Formula 1]
[0177] Diameter deviation (%) = │{(average diameter)-(measured diameter)} / (average diameter)×100│
[0178] [Formula 2]
[0179] Height deviation (%) = │{(average height)-(measured height)} / (average height)×100│
[0180]
Table 1
[0181] * The particle content is based on 100% by weight of the polyethylene terephthalate resin included in the core layer and the outer skin layer of the substrate film.
[0183] Referring to Table 1 above, when a laser with a wavelength of 1064 nm was irradiated for several milliseconds (ms) at a laser power range of 0.5 W to 10 W above the substrate film in the area where 100 thermal expansion domes were to be formed on the laser transfer film prepared by Examples 1 to 8, about 90 thermal expansion domes with an aspect ratio of 0.1 to 0.9 were formed. The deviations of the diameter and height of each thermal expansion dome were less than or equal to 5% and 6%, respectively.
[0184] In contrast, in Comparative Example 1, a PET substrate having no particles in the outer skin layer was used. When a laser having a wavelength of 1064 nm was irradiated for several milliseconds (ms) above the substrate film at a laser power range of 3 W to 9 W in the region of the heat-expandable light-absorbing layer 12 where 100 heat-expandable domes were to be formed on the laser transfer film prepared in Comparative Example 1, about 60 heat-expandable domes having an aspect ratio of 0.2 to 0.3 were formed. The deviations in diameter and height of each heat-expandable dome were 12% and 15%, respectively.
[0185] In addition, in Comparative Examples 2 and 3, a PET substrate having a particle content of 2.0 wt% in the outer skin layer was used. When a laser having a wavelength of 1064 nm was irradiated for several milliseconds (ms) above the substrate film at a laser power range of 0.5 W to 5 W or 0.5 W to 6 W with respect to the region of the heat-expandable light-absorbing layer 12 where 100 heat-expandable domes were to be formed on the laser transfer film prepared in Comparative Examples 2 and 3, about 60 heat-expandable domes having an aspect ratio of 0.7 to 0.9 were formed. The deviations of the diameter and height of each heat-expandable dome were greater than or equal to 11% and greater than or equal to 13%, respectively.
[0186] Compared with the laser transfer films produced by Examples 1 to 8, in the laser transfer films produced by Comparative Examples 1 to 3, since the lower limit or upper limit of the laser power for forming the thermal expansion dome increases, the laser power range is small and the number of thermal expansion domes formed is small.
[0187] Therefore, compared with the laser transfer films produced by Comparative Examples 1 to 3, in the laser transfer films produced by Examples 1 to 8, when irradiated with a laser having a wavelength of 1064 nm for several milliseconds (ms) within a larger laser power range, more thermal expansion domes with an aspect ratio of 0.1 to 0.9 were formed, and since the diameter and height deviations of each thermal expansion dome formed were small, it can be confirmed that the diameter and height of each thermal expansion dome are uniform.
[0188] Reference numerals
[0189] 10: Laser transfer film 11, 21: Base film
[0190] 12: heat-expandable light-absorbing layer 13, 23: adhesive layer
[0191] 20: Receiving film 22: Electrode layer
[0192] 23: Adhesive layer of receiving film 30: LED chip
[0193] C: cavity d: diameter t: Height TD: Thermal expansion dome
Claims
1. A laser transfer film, comprising: Base film; A heat-expandable light-absorbing layer; as well as Adhesive layer, The substrate film comprises one or more of inorganic particles and organic particles on at least one surface. When a laser having a wavelength of 1064 nm is irradiated on the substrate film for a time of less than or equal to 1 second at a laser power range of 0.5 W to 10 W, the heat-expandable light-absorbing layer and the adhesive layer expand to form a heat-expandable dome. The thermal expansion dome has a height-to-diameter ratio of 0.1 to 1.
2. The laser transfer film according to claim 1, wherein: When a region where 100 heat expansion domes are to be formed is irradiated with a picosecond laser or a nanosecond laser in a laser power range of 0.5 W to 10 W, the heat expandable light absorbing layer and the adhesive layer form 70 or more heat expansion domes.
3. The laser transfer film according to claim 1, wherein: The light transmittance of the substrate film at a wavelength of 550 nm is greater than or equal to 85%.
4. The laser transfer film according to claim 1, wherein: The ten-point average roughness (Rz) of the surface of the substrate film is 0.5 μm to 8 μm.
5. The laser transfer film according to claim 1, wherein: The particles include inorganic particles comprising one or more selected from silicon dioxide, calcium carbonate, titanium carbide and zirconium oxide; or The organic particles contain one or more selected from styrene resin, acrylic resin, olefin resin, and copolymer resins thereof.
6. The laser transfer film according to claim 1, wherein: The thermal conductivity of the particles is greater than or equal to 1.4 W / m·K.
7. The laser transfer film according to claim 1, wherein: The substrate film comprises: A polyester resin core layer; and A polyester resin outer layer, which comprises one or more inorganic particles and organic particles on at least one surface of the polyester resin core layer, The content of the particles is 0.01 wt % to 1.0 wt % based on 100 wt % of the polyester resin included in the core layer and the outer skin layer.
8. The laser transfer film according to claim 1, wherein: The heat-expandable light-absorbing layer includes a binder and a light absorber, The light absorber includes a near-infrared absorption dye having a maximum absorption wavelength of 900 nm to 1200 nm.
9. The laser transfer film according to claim 8, wherein: The content of the light absorber is 0.1 parts by weight to 30 parts by weight based on 100 parts by weight of the heat expandable light absorbing layer.
10. The laser transfer film according to claim 1, wherein: The coating amount of the heat-expandable light-absorbing layer after drying is 0.5 g / m 2 Up to 9g / m 2 .
11. The laser transfer film according to claim 1, wherein: The heat-expandable light-absorbing layer has a thickness of 0.4 μm to 10 μm.
12. The laser transfer film according to claim 1, wherein: The heat-expandable light-absorbing layer and the adhesive layer are separated by expansion to form a plurality of heat-expandable domes. The diameter deviation of the plurality of thermal expansion domes according to the following formula 1 is less than or equal to 10%. [Formula 1] Diameter deviation (%) = │{(average diameter)-(measured diameter)} / (average diameter)×100│ 13. The laser transfer film according to claim 12, wherein: The height deviation of the plurality of thermal expansion domes according to the following formula 2 is less than or equal to 10%. [Formula 2] Height deviation (%) = │{(average height)-(measured height)} / (average height)×100│ 14. The laser transfer film according to claim 12, wherein: The thickness of the adhesive layer is 0.5 to 6 times the thickness of the heat-expandable light-absorbing layer.
15. The laser transfer film according to claim 1, further comprising: The transfer body is bonded to the surface of the adhesive layer.
16. The laser transfer film according to claim 15, wherein: The transfer body includes a semiconductor chip.
Citation Information
Patent Citations
Donor element for thermal transfer
CN101044032A
Laser induced transfer film
CN112009128A
Thermal transcription sheet forming raised picture, method for forming raised picture, raised picture product
JP1998151870A
Outdoor type Automated External Defibrillator storage box
KR1020220043435A
Cited By
Efficient laser thermal transfer ribbon based on gas pressure driving ink layer
CN120039055A
